Treatment of Learning Anxiety: A Bibliometric Review in Islamic Psychology - Winarso, Widodo; Riyanto, Onwardono Rit (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study provides a bibliometric review of research on the treatment of learning anxiety in Islamic psychology, which involved a systematic search in multiple databases, resulting in 91 relevant studies for analysis. The bibliometric data generated from the investigation, identification, and extraction processes were analyzed using statistical analysis. The study found that cognitive behavioral therapy, acceptance and commitment therapy, and stress reduction therapy were the most commonly used methods to treat learning anxiety. Furthermore, most studies were conducted in the United Kingdom and the United States, which suggests a need for further research in other regions. Studies found that the most frequently discussed topics on treating learning anxiety in Islamic psychology were psychological interventions, educational practices, and the impact of Islamic beliefs and practices on learning anxiety. Additionally, the study identified variations in the quality of studies, with some demonstrating high quality while others indicating a risk of bias. This paper emphasizes the importance of conducting further research on the treatment of learning anxiety in Islamic psychology, particularly in other regions. These findings could be valuable for academics, researchers, and psychology practitioners interested in treating learning anxiety and educators seeking to better understand and address this issue in their students. Further studies can focus on developing therapy models tailored to Islamic Psychology's principles to provide more optimal outcomes in addressing learning anxiety.